Ginkgo biloba extract protects against ionizing radiation-induced oxidative organ damage in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ATASOY, BESTE MELEK; ERZİK, CAN; ŞENER, GÖKSEL; KABASAKAL, LEVENT (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2006)
The present study was designed to determine the possible protective effects of Ginkgo biloba extract (EGb) against oxidative organ damage induced by irradiation (IR). Sprague-Dawley rats were exposed to whole-body IR (800cGy) after a 15-day pretreatment with either saline or EGb (50 mg/kg/day), intraperitoneally, and treatments were repeated immediately after the IR. Then the rats were decapitated at either 6 h or 72 It after IR, where EGb or saline injections were repeated once daily. Lung, liver, kidney and ileum samples were obtained for the determination of malondialdehyde, glutathione levels, myeloperoxidase activity and collagen contents, while oxidant-induced DNA fragmentation was evaluated in the ileal tissues. All tissues were also examined microscopically and assayed for the production of reactive oxidants using chemiluminescence (CL). Lactate dehydrogenase (LDH)-an indicator of tissue damage and TNF-alpha were assayed in serum samples. In the saline-treated irradiation groups, glutathione levels were decreased significantly, while the malondialdehyde levels, myeloperoxidase activity and collagen content were increased in the tissues (p < 0.01-0.001), which were in parallel with the increases in luminol and lucigenin CL values. In the EGb treated-IR groups, all of these oxidant responses were prevented significantly (p < 0.05-0.01). LDH and TNF-alpha levels, which were increased significantly (p < 0.01-0.001) following IR, were decreased (p < 0.05-0.001) with EGb treatment. In conclusion, the present data demonstrate that EGb, through its free radical scavenging and antioxidant properties, attenuates irradiation-induced oxidative organ injury, suggesting that EGb may have a potential benefit in enhancing the success of radiotherapy. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: irradiation; lipid peroxidation; glutathione; myeloperoxidase; Ginkgo biloba; NITRIC-OXIDE; EGB 761; REACTIVE OXYGEN; SUPEROXIDE-DISMUTASE; FREE-RADICALS; IN-VIVO; STRESS; MECHANISMS; FIBROSIS; INJURY